Primary CNS lymphoma at first relapse/progression: characteristics, management, and outcome of 256 patients from the French LOC network. Issue 9 (1st September 2016) - Langner-Lemercier, Sophie; Houillier, Caroline; Soussain, Carole; Ghesquières, Hervé; Chinot, Olivier; Taillandier, Luc; Soubeyran, Pierre; Lamy, Thierry; Morschhauser, Franck; Benouaich-Amiel, Alexandra; Ahle, Guido; Moles-Moreau, Marie-Pierre; et al.
Abstract: Background: Treatment of relapsed/refractory (R/R) primary CNS lymphoma (PCNSL) is poorly defined, because randomized trials and large studies are lacking. The aim of this study was to analyze the characteristics, management, and outcome of R/R PCNSL patients after first-line therapy in a nationwide cohort. Methods: We analyzed R/R PCNSL patients following first-line treatment who had been prospectively registered in the database of the French network for oculocerebral lymphoma (LOC) between 2011 and 2014. Results: Among 563 PCNSL patients treated with first-line therapy, we identified 256 with relapsed ( n = 93, 16.5%) or refractory ( n = 163, 29.0%) disease. Patients who were asymptomatic at relapse/progression (25.5%), mostly diagnosed on routine follow-up neuroimaging, tended to have a better outcome. Patients who received salvage therapy followed by consolidation (mostly intensive chemotherapy plus autologous hematopoietic stem cell transplantation [ICT + AHSCT]) experienced prolonged survival compared with those who did not receive salvage or consolidation therapy. Independent prognostic factors at first relapse/progression were: KPS ≥ 70 vs KPS < 70), sensitivity to first-line therapy (relapsed vs refractory disease), duration of first remission (progression-free survival [PFS] ≥1 y vs <1 y), and management at relapse/progression (palliative care vs salvage therapy). Patients who relapsed early after first-line therapy (ie, PFS < 1 y) had a poor outcome, comparable to that of refractory patients. Conversely, patients experiencing late relapses (PFS ≥ 1 y) and/or undergoing consolidation with ICT + AHSCT experienced prolonged survival. Conclusions: About a third of PCNSL patients are primary refractory to first line treatment. We identified several independent prognostic factors that can guide the management of R/R PCNSL patients.